2017
DOI: 10.1080/19381980.2017.1279768
|View full text |Cite
|
Sign up to set email alerts
|

Multiple fractures in infants who have Ehlers-Danlos/hypermobility syndrome and or vitamin D deficiency: A case series of 72 infants whose parents were accused of child abuse and neglect

Abstract: Objective: To increase the level of awareness that Ehlers-Danlos/hypermobility syndrome (EDS) and vitamin D deficiency are associated with infantile fragility fractures and radiologic features that may be mistakenly reported to be caused by non-accidental trauma due to Child Abuse and Neglect (CAN).Patients and Methods: We constructed a case series, the largest to date, of infants with EDS who were vitamin D sufficient, insufficient and deficient and infants without EDS but with documented vitamin D deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 71 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…Case series have shown that joint hypermobility and the joint hypermobile form of Ehlers-Danlos syndrome (EDStype 3) are overrepresented in the parents of infants with MUF and in the infants themselves [55,56].…”
Section: Ehlers-danlos Syndrome/joint Hypermobility In Parents And/ormentioning
confidence: 99%
“…Case series have shown that joint hypermobility and the joint hypermobile form of Ehlers-Danlos syndrome (EDStype 3) are overrepresented in the parents of infants with MUF and in the infants themselves [55,56].…”
Section: Ehlers-danlos Syndrome/joint Hypermobility In Parents And/ormentioning
confidence: 99%
“…EDS and EDS hypermobility type increases the risk of fractures in adults [25, 26] due to low bone mass and abnormal bone structures [25]. A case series suggested that there is an association between parental Ehlers-Danlos/hypermobility syndrome and multiple fractures in infancy [27]. Genome-wide association studies indicate that pediatric bone mass is largely determined by genetics [22], and this aspect is thus of importance for MBD.A skeletal survey is recommended for the evaluation of suspected infant abuse as there is strong evidence to indicate that injury to the long bone and rib fractures are particularly liable to be due to abuse mechanisms [28].…”
Section: Introductionmentioning
confidence: 99%
“…Low vitamin D levels without association of radiographic evidence of infantile rickets does not cause fractures (Servaes et al, 2016). The flawed theories that EDS or EDS combined with low vitamin D cause "fragility fractures" (Holick et al, 2017) are not evidence-based, and these diagnoses appear to have stemmed from courtroom defense arguments rather than clinical purposes and practice. Such unfounded theories should not be the basis of expert testimony (Paul, Narang, & Committee on Medical Liability and Risk Management, 2017;Tinkle, 2019).…”
Section: Some Studies Of Adult Eds Patients Suggest a Risk Of Low Bonementioning
confidence: 99%
“…The only published case series suggesting that infants with EDS are fragile (Holick, Hossein-Nezhad, & Tabatabaei, 2017) consists entirely of infants previously diagnosed as victims of abuse and does not contain accurate scientific methods, data, legitimate peer-review, or conclusions. However, the false claim that a child has "EDS/OI/EDS and vitamin D deficiency/infantile rickets associated with fragility fractures in infants that can be misinterpreted as … child abuse."…”
mentioning
confidence: 99%